2010
DOI: 10.1146/annurev-genom-082509-141811
|View full text |Cite
|
Sign up to set email alerts
|

Patents in Genomics and Human Genetics

Abstract: Genomics and human genetics are scientifically fundamental and commercially valuable. These fields grew to prominence in an era of growth in government and nonprofit research funding, and of even greater growth of privately funded research and development in biotechnology and pharmaceuticals. Patents on DNA technologies are a central feature of this story, illustrating how patent law adapts---and sometimes fails to adapt---to emerging genomic technologies. In instrumentation and for therapeutic proteins, paten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 99 publications
0
54
0
Order By: Relevance
“…22, 39, 40 Oldman 40 searched for trends in patent claims in genomics, proteomics, and biotechnology by using keywords in the Espacenet titles such as genes, proteins, DNA, amino acids, nuclide nucleic acids, and RNA in the time period 1990–2003. Unfortunately, as this study used a different method the results are difficult to compare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22, 39, 40 Oldman 40 searched for trends in patent claims in genomics, proteomics, and biotechnology by using keywords in the Espacenet titles such as genes, proteins, DNA, amino acids, nuclide nucleic acids, and RNA in the time period 1990–2003. Unfortunately, as this study used a different method the results are difficult to compare.…”
Section: Discussionmentioning
confidence: 99%
“…A famous case is the commercial company Myriad, which has the rights to commercialize specific hereditary breast cancer genes. 22 For several years now, people have objected to these patents due to the potential impact on diagnostic testing. 23, 24 However, in June 2013, the Supreme Court decided in the Myriad case that human genes, defined as genomic DNA, are not patentable 25, 26, 27…”
Section: Introductionmentioning
confidence: 99%
“…Issues surrounding the appropriate disclosure and use of NGS data, necessary adaptations of patent law to facilitate the clinical use of NGS technologies, and establishment of insurance reimbursement protocols for NGS testing must also be addressed in the coming years to enable society to embrace the transition to a post-genomic era of medicine (87)(88)(89).…”
Section: Political and Social Issuesmentioning
confidence: 99%
“…As noted by Cook-Deegan and Heaney, a "single blocking patent on a normal gene or any common disease-associated variant can be sufficient, if exclusively licensed to just one provider, to limit testing by other laboratories for that clinical condition." 34 The validity of such claims however is in doubt following the US Supreme Court's decision in Mayo v. Prometheus 35 from March 2012, i.e., after 23andMe's patent application was accepted but before it was granted. In that case, the Supreme Court found that methods that are based on "laws of nature" are not patentable.…”
Section: Original Research Articlementioning
confidence: 99%